Diversity and species composition of click beetles (Coleoptera: Elateridae) at different land-use types in Harapan Rainforest landscape, Jambi, Indonesia. Issue 1 (March 2020) - Kasmiatun; Nazarreta, R; Hidayat, P; Buchori, D
Abstract: Click beetles (Family Elateridae) are the largest family of beetles (Order Coleoptera) in superfamily Elateroidea that play an important role in the ecosystem, either as herbivores, predators and rhizophag. Land-use change can have a negative effect on diversity and abundance of click beetles. The aim of this research was to study the diversity and species composition of click beetles at different land-use types in Jambi. This research was carried out in Harapan Rainforest landscape that consists of 4 different land-use, i.e forest, jungle rubber, rubber plantation, and oil palm plantation. Click beetles were collected by fogging method in the morning and fogger directed toward the higher canopy for 20 min. The insect was collected in 16 traps that were installed under plant canopy, then the sample was sorted and identified in the laboratory. In a total of 2.042 individuals click beetles were collected, belonging to 7 subfamilies, 23 genera, and 59 morphospecies. Species richness and abundance of click beetles were higher in forest systems, while the lowest species richness was found in oil palm plantation and the lowest abundance was found in rubber plantation. Common click beetles species found in each land-use have consisted of morphospecies Melanoxanthus sp.01 (Elaterinae: Melanoxanthus ). This research showed that different land-use types in Harapan Rainforest influenced the diversity, abundance, and species composition of click beetles. In conclusion, that habitat transformation has an impact on the loss of click beetles communities.